Promising Health Benefits of Hippophae rhamnoides L. (Sea Buckthorn): A Miracle Plant - Mehta, Madhuri; Gupta, Vijayta; Kant, Vinay; Varshneya, Chandresh (Asian Journal of Science and Applied Technology, 2019)
Seabuckthorn (Hippophae rhamnoides L.), a spiny bush plant native to Europe and Asia, have many nutritional and medicinal properties. All parts of this plant are rich source of bioactive components such as, tocopherols, carotenoids, flavonoids, vitamins, sugar, organic acids and minerals. Various in vivo and in vitro studies on animals and human suggest that seabuckthorn has many beneficial effects as cardioprotective, antiatherogenic, antioxidant, anticancer, immunomodulatory, anti-bacterial, antiviral and anti-inflammatory, which reveals its medicinal and pharmacological properties. Seabuckthorn can be supplemented as nutraceuticals in animal feed to enhance its antioxidative potential, strengthen the immune system, which may help the organism to resist stress. To promote the large scale utilization of seabuckthorn, it would be worthwhile to perform more research on this plant.